Clinical, Radiographic And Bronchoscopic Findings of Tracheal Collapse in A Calf - TÜMER, Kenan Çağrı; POLAT, Eren (Journal of the Hellenic Veterinary Medical Society, 2022)
A six-day-old calf was presented to the XXX University Veterinary Teaching Hospital with a history of wheezing (noisy respiration), dyspnea that worsens with exercise and drinking. The calf shown upper respiratory tract symptoms including extended head and neck, dilated nostrils, severe inspiratory stridor with characteristic “honking” sound, and exophthalmos. Upon these findings, we suspected upper airway obstruction and decided to perform cervical-thoracal radiography and bronchoscopy to obtain detailed visualization of the upper respiratory tract. On the thorax radiograph, significant tracheal narrowing was visible at the thoracic inlet, and it was beginning at the caudal cervical region (C5) and extending to the cranial thorax (T1). Also, severe dorsoventrally narrowing was displayed approximately 15 cm after entering the trachea using bronchoscopy. The tracheal collapse was diagnosed in this case based on clinical, radiographical, and bronchoscopy findings. It is important to remember that tracheal collapse should be considered in the differential diagnosis in calves that show upper respiratory tract symptoms such as extended head and neck, dilated nostrils, severe inspiratory stridor with characteristic “honking” sound.